DC/AC fundamentals a systems approach - Floyd, Thomas L.; Buchla, David M. (Boston Pearson, 2013)
For courses in Electronics and Electricity Technology DC/AC Fundamentals: A Systems Approach takes a broader view of DC/AC circuits than most standard texts, providing relevance to basic theory by stressing applications of dc/ac circuits in actual systems.
1. DC circuits -- Systems, quantities, and units -- Voltage, current, and resistance -- Ohm's law, energy, and power -- Series circuits -- Parallel circuits -- Series-parallel circuits -- Magnetism and electromagnetism -- 2. AC circuits -- Introduction to alternating current and voltage -- Capacitors -- RC circuits -- Inductors -- RL circuits -- RLC circuits and resonance -- Transformers -- Time response of reactive circuits.
Keywords: Electric circuits